2022
DOI: 10.3390/genes13040559
|View full text |Cite
|
Sign up to set email alerts
|

Variable Clinical Appearance of the Kir2.1 Rare Variants in Russian Patients with Long QT Syndrome

Abstract: Background: The KCNJ2 gene encodes inward rectifier Kir2.1 channels, maintaining resting potential and cell excitability. Presumably, clinical phenotypes of mutation carriers correlate with ion permeability defects. Loss-of-function mutations lead to QTc prolongation with variable dysmorphic features, whereas gain-of-function mutations cause short QT syndrome and/or atrial fibrillation. Methods: We screened 210 probands with Long QT syndrome for mutations in the KCNJ2 gene. The electrophysiological study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Mutation V93I is associated with familial atrial fibrillation and can lead to increased channel activity ( Xia et al, 2005 ). In vitro analysis of channel function revealed a gain-of-function for this variant ( Xia et al, 2005 ; Zaklyazminskaya et al, 2022 ). A study of Russian patients with this variant revealed a surprising phenotype without any signs of ATS1 or mild but evident QTc prolongation ( Zaklyazminskaya et al, 2022 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Mutation V93I is associated with familial atrial fibrillation and can lead to increased channel activity ( Xia et al, 2005 ). In vitro analysis of channel function revealed a gain-of-function for this variant ( Xia et al, 2005 ; Zaklyazminskaya et al, 2022 ). A study of Russian patients with this variant revealed a surprising phenotype without any signs of ATS1 or mild but evident QTc prolongation ( Zaklyazminskaya et al, 2022 ).…”
Section: Resultsmentioning
confidence: 96%
“…In vitro analysis of channel function revealed a gain-of-function for this variant ( Xia et al, 2005 ; Zaklyazminskaya et al, 2022 ). A study of Russian patients with this variant revealed a surprising phenotype without any signs of ATS1 or mild but evident QTc prolongation ( Zaklyazminskaya et al, 2022 ). Thus, the clinical significance of this variant remains unclear; however, it is classified as a potential proarrhythmogenic risk factor.…”
Section: Resultsmentioning
confidence: 96%